Disadvantages of Using Modern Technologies in the Legal Field - Abd, Manal; Rasheed, Saba (Journal of Legal Sciences, 2026)
The legal field is currently facing rapid transformations due to the integration of modern technologies into most of its specializations. Despite the efficiency, speed, and accuracy these tools provide in data processing, they pose serious challenges that threaten the fundamental principles of rights and freedoms that various legal systems were established to preserve and protect. Foremost among these rights, which have expanded in the digital sphere, is the right to digital privacy. This is due to the use of vast amounts of personal and professional information, which exposes it to the risk of hacking or misuse. The right to equality and non-discrimination in algorithms has emerged as a result of algorithms relying on historical data or biased information, which may lead to unfair or biased results. Therefore, these challenges require the establishment of strict legal and regulatory frameworks that balance the benefits of modern technologies with the protection of the fundamental rights of individuals.